PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN(STUDI PADA PAKAIAN MEREK ZARA) - Riani Winarni; Tri Sanatha Wahyu Akbar; Umban Adi Jaya; Galih Raspati; Melati Peronika Simanjuntak; Fahrurrazi Fahrurrrazi (MBA Journal – Management, Business Administration, and Accounting Journal, 2025)
This study aims to determine the effect of product quality and promotion on consumer decisions Bentenan Center Sonder Minahasa. This research methodology uses purposive sampling quantitative research approach. The sampling technique used is with a sample of 70 respondents. Data collection techniques were carried out by conducting field observations and distributing respondent questionnaires, using multiple linear regression.The statistical test carried out in this study were validity test, determination tests, partial tests and simultan tests. Throught the validity and reliability tests, it was found that the questionnaire in this study was valid and reliable and promotion of 94,5% while the remaining 5.5% is influenced by other variable not examined in this study. Overall product quality and promotion together have a positive on purchasing decisions.